A comparative study about corrosion resistance and biocompatibility of Ti6Al4V samples produced by wrought and additive manufacturing methods - Gurkan, Doruk; Sagbas, Binnur; Uzunsoy, Deniz; Dalbayrak, Basak; Arisan, Elif Damla (ELSEVIER SCIENCE SA, 2026)
Ti6Al4V is widely used in biomedical applications due to its excellent mechanical properties and biocompatibility. Conventional manufacturing techniques, such as plastic deformation processes, have long been employed to produce Ti6Al4V implants and prosthetics. Recently, the advent of additive manufacturing (AM), which allows the generation of complex geometries and customized implants, has introduced a new dimension to the production of these biomedical devices. However, examining the effects of newly developed manufacturing methods on material and sample properties is extremely important to obtain successful products. In this study, additive manufactured and wrought Ti6Al4V samples were implemented for their corrosion resistance and biocompatibility as orthopedic implant material. Three different post processes such as sandblasting, acid etching and bioactive coating (hydroxyapatite-chitosan composite via electrophoretic deposition (EPD)) were applied on the additive manufactured sample surfaces, while only the bioactive coating was applied on the wrought sample surfaces and their effects on the corrosion and biocompatibility were evaluated with the reference of untreated control samples. Corrosion resistance properties were examined with open circuit potential (OCP) measurement, electrochemical impedance spectroscopy (EIS) and Tafel extrapolation, respectively. Electrochemical impedance spectroscopy and Tafel extrapolation showed similar results. Biocompatibility tests were carried out as mouse embryonic fibroblast (MEF) cell culture and cellular viability tests with mouse embryonic fibroblast cells. Coating and sandblasting were the best post-processing methods for anti-corrosion and biocompatibility applications. AM sandblasted samples are the most suitable samples for both application areas.
Keywords: Laser powder bed fusion; Biomedical; Surface treatment; Ti6Al4V; Biocompatibility; Corrosion; TITANIUM; ALLOYS; COATINGS; BEHAVIOR; STEEL; Materials Science